2017
DOI: 10.3390/molecules22040635
|View full text |Cite
|
Sign up to set email alerts
|

Na+i,K+i-Dependent and -Independent Signaling Triggered by Cardiotonic Steroids: Facts and Artifacts

Abstract: Na+,K+-ATPase is the only known receptor of cardiotonic steroids (CTS) whose interaction with catalytic α-subunits leads to inhibition of this enzyme. As predicted, CTS affect numerous cellular functions related to the maintenance of the transmembrane gradient of monovalent cations, such as electrical membrane potential, cell volume, transepithelial movement of salt and osmotically-obliged water, symport of Na+ with inorganic phosphate, glucose, amino acids, nucleotides, etc. During the last two decades, it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 178 publications
(265 reference statements)
3
15
0
Order By: Relevance
“…Convallatoxin-induced inhibition of viral protein translation by methionine transport reduction is not the only mechanism attributed to the antiviral activity of cardiac glycosides. Alternate mechanisms of action are based on the ability of these compounds to modulate cell signalling pathways [370]. For example, cardiac glycoside digitoxin has been reported to inhibit HCMV through induction of cellular autophagy following activation of the regulatory kinase AMPK via a novel NA + ,K + -ATPase subunit α1-AMPK-ULK1 pathway [173].…”
Section: Cardiac Glycosidesmentioning
confidence: 99%
“…Convallatoxin-induced inhibition of viral protein translation by methionine transport reduction is not the only mechanism attributed to the antiviral activity of cardiac glycosides. Alternate mechanisms of action are based on the ability of these compounds to modulate cell signalling pathways [370]. For example, cardiac glycoside digitoxin has been reported to inhibit HCMV through induction of cellular autophagy following activation of the regulatory kinase AMPK via a novel NA + ,K + -ATPase subunit α1-AMPK-ULK1 pathway [173].…”
Section: Cardiac Glycosidesmentioning
confidence: 99%
“…Importantly, while the current review has focused primarily on the non-ion dependent signaling mechanisms of the NKA, the [Na + ]i/[K + ]i ratio has been shown to also initiate similar signaling events. A number of important studies have shown the role of NKA inhibition and elevation of the [Na + ]i/[K + ]i ratio in the activation of Src-EGFR-MAPK- and Akt-mediated signaling pathways triggered by CTS, and readers are referred to a recent review which more thoroughly addresses this topic [ 83 ]. The importance of this concept is highlighted by recent data showing that NKA inhibition by CTS triggers TGFβ-induced fibrosis in cultured human lung fibroblasts via [Na + ]i/[K + ]i-mediated signaling which results in augmented expression of COX-2 [ 84 ] and downregulation of TGFβ2R [ 85 ].…”
Section: Cts (Cardiotonic Steroids) Nka and Fibrosismentioning
confidence: 99%
“…An increase in [Na + ] i suppresses Ca 2+ extrusion via the Na + /Ca 2+ exchanger (NCX), thereby elevating intracellular Ca 2+ concentrations (Baker et al, 1969;Blaustein and Hamlyn, 2020;Pavlovic, 2020). An increase in [Na + ] i may also stimulate Na + -sensitive signaling pathways (Kuroki et al, 1997), while a decrease in [K + ] i suppresses protein translation (Orlov et al, 2017;Amarelle et al, 2019;Klimanova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%